Designing things a critical introduction to the culture of objects - Boradkar, Prasad (Berg, 2010)
"When and why did the turntable morph from playback device to musical instrument? Why have mobile phones evolved changeable skins? How many meanings can one attach to such mundane things as tennis balls? The answers to such questions illustrate this provocative book, which examines the cultural meanings of things and the role of designers in their design and production. Designing Things provides the reader with a map of the rapidly changing field of design studies, a subject which now draws on a diverse range of theories and methodologies - from philosophy and visual culture, to anthropology and material culture, to media and cultural studies.With clear explanations of key concepts - such as form language, planned obsolescence, object fetishism, product semantics, consumer value and user needs - overviews of theoretical foundations and case studies of historical and contemporary objects, Designing Things looks behind-the-scenes and beneath-the-surface at some of our most familiar and iconic objects."--pub. website.